´Impacto Socioeconómico de la Explotación Minera de la Empresa Ecuacorriente S.A, en el Cantón El Pangui, Provincia de Zamora Chinchipe, Año 2016 - Cabrera Machuca, Sayury Guisela (2017)
In the present investigation the social and economic impact of the exploitation activities of the El Pangui project was determined. It was defined in the variables income, employment, tax revenues of the Autonomous Government Decentralized of the canton El Pangui and other social and environmental things. The Mirador project is one of the five strategic projects in the mining sector that the Ecuadorian government has promoted in the search for the benefits generated for the country in general and for the area of influence in particular in the canton El Pangui. The beginning of mining activities came hand in hand with a series of problems, mainly with the Shuar people historically settled in these properties, initiating their mining activities without prior, free and informed consultation with the indigenous communities, in breach of which guarantees the Constitution; putting at risk the sustainability of water, land and biodiversity, destroying all forms of livelihood, forcing community members and their families to leave their homes and workplaces, as well as to avoid promises of consumption and safe jobs made by the mining company. The present investigation was characterized by being descriptive because it focused on knowing the reality of the study itself, through the exact description of the results that determine it to infer about its behavior, for the effect is used field research, information secondary education provided by institutions involved in the mining sector and bibliographic information. The present study has shown that the implementation of the project has not had a significant positive impact on the income or employment of the inhabitants of the canton El Pangui; however, has generated a significant increase in tax revenues to local government, but have produced social impacts such as population polarization on the mining issue, evictions, crime, insecurity and environmental problems are already glimpsed by pollution of air and water